DIFFERENCES IN EFFECT AND METHOD OF EXERCISE BLOCKED PRECTISE ABILITY TO PRACTICE RANDOM FIELD BASED ON TENNIS GRONDSTROKE BASED ON KINESTHETIC PERCEPTION - FRURY, F. (Journal Of Indonesia Sport Education and Adapted Physical Education (JISEAPE), 2019)
Sport is all systematic activities to encourage, support and develop the potential physical, spiritual, and mental. (Act No. 3 year 2005). National sports destination according to law no. 3 2005, chapter 4, which reads "national sports aims to maintain and improve health and fitness, achievement, human qualities, inculcate moral values and noble character, sportsmanship, discipline, cultivate and foster national unity, strengthen national defence, as well as raise the dignity , dignity and honor of the nation ". To achieve the national goal No 3 scope of coaching and sports development include: 1) a health education, 2) recreational sports, 3) sporting achievement. There is no information difference approach to exercise influence,groundstrokes tennis courts.So that the movement can be done efficiently, then a tennis player must have a good physical condition. Physical ability alone there are an assortment needed to support the movement. Various physical ability is speed of reaction, strength, endurance, speed, flexibility and kinesthetic perception. In the development of tennis groundstrokes ability, but must be supported by excellent physical condition, then in the process of training the trainer should be able to choose the learning approach is appropriate or correct.Based on the background issues that have been pointed out, the authors are interested in conducting research titled "Differences Influence Approach Exercise and Kinesthetic Perception Of Groundstroke Tennis Skills(Experimental Study on Student Men Sports Coaching Education Department of the Faculty of Teaching and Education University Development Branch Surakarta). "